Metal and Metal Oxide Based Advanced Ceramics for Electrochemical Biosensors-A Short Review - Subbaiah, G. Bala; Ratnam, K. Venkata; Janardhan, S.; Shiprath, K.; Manjunatha, H.; Ramesha, M.; Prasad, N. V. Krishna; Ramesh, S.; Babu, T. Anil (Frontiers in Materials, 2021)
Identifying and quantifying the biological concentrations of certain biomolecules such as dopamine, glucose, tyrosine, and cholesterol, etc. has become the basis for medical diagnosis in the treatment of a number of related diseases. In most cases, the concentrations of these biomolecules in biofluids like blood acts as a biomarker and becomes crucial in the treatment of diseases. On the other hand, advanced ceramics refers to oxides (alumina, zirconia), non-oxides: (carbides, borides, nitrides, silicides), Composites (particulate reinforced combinations of oxides and non-oxides), etc. This review article discusses recent developments in the field of electrochemical sensors developed using metal and metal oxide based advanced ceramics with an emphasis on developments in the field over the past five years. The article presents the key results, important findings, and interesting chemistry of biosensing advanced ceramic based electrochemical biosensors for some important biomolecules such as acetaminophen, glucose, and dopamine, etc.